Boredom, art, and activism: notes on the experiences of people with disabilities in Mexico during the COVID-19 pandemic - Miranda-Galarza, Beatriz; Mayer-Foulkes, Benjamín (Frontiers in Sociology, 2023)
During the confinement due to the COVID-19 pandemic, people with disabilities in Mexico were faced with conditions that, however, did not vary from those experienced daily. The pandemic boredom experienced by most of the general population was not foreign to this population. Unfortunately, the taboos around both boredom and disability limited reflection and questioning about it. In this perspective article, a brief tour is made regarding the encounters and disagreements of these two categories in the lives of people with disabilities during confinement in Mexico. The objective is to make visible, briefly, some relevant elements for reflection, and through this, to call for critical and in-depth research on the matter.